Effects of presentation level on speech-on-speech masking by voice-gender difference and spatial separation between talkers - Oh, Yonghee; Friggle, Phillip; Kinder, Josephine; Tilbrook, Grace; Bridges, Sarah E. (Frontiers in Neuroscience, 2023)
Many previous studies have reported that speech segregation performance in multi-talker environments can be enhanced by two major acoustic cues: 1) voice-characteristic differences between talkers; 2) spatial separation between talkers. Here, the improvement they can provide for speech segregation is referred to as “release from masking”. The goal of this study was to investigate how masking release performance with two cues is affected by various target presentation levels. Sixteen normal-hearing listeners participated in the speech recognition in noise experiment. Speech-on-speech masking performance was measured as the threshold target-to-masker ratio needed to understand a target talker in the presence of either same- or different-gender masker talkers to manipulate the voice-gender difference cue. These target-masker gender combinations were tested with five spatial configurations (maskers co-located or 15°, 30°, 45°, and 60° symmetrically spatially separated from the target) to manipulate the spatial separation cue. In addition, those conditions were repeated at three target presentation levels (30, 40, and 50 dB sensation levels). Results revealed that the amount of masking release by either voice-gender difference or spatial separation cues was significantly affected by the target level, especially at the small target-masker spatial separation (±15°). Further, the results showed that the intersection points between two masking release types (equal perceptual weighting) could be varied by the target levels. These findings suggest that the perceptual weighting of masking release from two cues is non-linearly related to the target levels. The target presentation level could be one major factor associated with masking release performance in normal-hearing listeners.